Impact of screening and relaxation on weakly coupled two-dimensional heterostructures - Nguyen, T. T. Nhung; Sollfrank, T.; Tegenkamp, C.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Potassium titanyl phosphate Z- and Y-cut surfaces from density-functional theory - Neufeld, Sergej; Bocchini, Adriana; Schmidt, Wolf Gero (Physical Review Materials)

Surface localized phonon modes at the Si(553)-Au nanowire system - Plaickner, Julian; Speiser, Eugen; Braun, Christian; Schmidt, Wolf Gero; Esser, Norbert; Sanna, Simone (Physical Review B)

GaInP/AlInP(001) Interfaces from Density Functional Theory - Meier, Lukas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

InP and AlInP(001)(2 × 4) Surface Oxidation from Density Functional Theory - Ruiz Alvarado, Isaac Azahel; Karmo, Marsel; Runge, Erich; Schmidt, Wolf Gero (ACS Omega)

Controlled growth of ordered monolayers of N-heterocyclic carbenes on silicon - Franz, Martin; Chandola, Sandhya; Koy, Maximilian; Zielinski, Robert; Aldahhak, Hazem; Das, Mowpriya; Freitag, Matthias; Gerstmann, Uwe; Liebig, Denise; Hoffmann, Adrian Karl; Rosin, Maximilian; Schmidt, Wolf Gero; et al. (Nature Chemistry)

Polaronic enhancement of second-harmonic generation in lithium niobate - Kozub, Agnieszka L.; Schindlmayr, Arno; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)
Density-functional theory within a Berry-phase formulation of the dynamical polarization is used to determine the second-order susceptibility χ(2) of lithium niobate (LiNbO3). Defect trapped polarons and bipolarons are found to strongly enhance the nonlinear susceptibility of the material, in particular if localized at NbV–VLi defect pairs. This is essentially a consequence of the polaronic excitation resulting in relaxation-induced gap states. The occupation of these levels leads to strongly enhanced χ(2) coefficients and allows for the spatial and transient modification of the second-harmonic generation of macroscopic samples.

Band Alignment at Ga x In 1– x P/Al y In 1– y P Alloy Interfaces from Hybrid Density Functional Theory Calculations - Meier, Lukas; Braun, Christian; Hannappel, Thomas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Vibrational Raman spectroscopy on adsorbate-induced low-dimensional surface structures - Speiser, Eugen; Esser, Norbert; Halbig, Benedikt; Geurts, Jean; Schmidt, Wolf Gero; Sanna, Simone (Surface Science Reports)

Free and defect-bound (bi)polarons in LiNbO3: Atomic structure and spectroscopic signatures from ab initio calculations - Schmidt, Falko; Kozub, Agnieszka L.; Biktagirov, Timur; Eigner, Christof; Silberhorn, Christine; Schindlmayr, Arno; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)
Polarons in dielectric crystals play a crucial role for applications in integrated electronics and optoelectronics. In this work, we use density-functional theory and Green's function methods to explore the microscopic structure and spectroscopic signatures of electron polarons in lithium niobate (LiNbO3). Total-energy calculations and the comparison of calculated electron paramagnetic resonance data with available measurements reveal the formation of bound polarons at Nb_Li antisite defects with a quasi-Jahn-Teller distorted, tilted configuration. The defect-formation energies further indicate that (bi)polarons may form not only at Nb_Li antisites but also at structures where the antisite Nb atom moves into a neighboring empty oxygen octahedron. Based on these structure models, and on the calculated charge-transition levels and potential-energy barriers, we propose two mechanisms for the optical and thermal splitting of bipolarons, which provide a natural explanation for the reported two-path recombination of bipolarons. Optical-response calculations based on the Bethe-Salpeter equation, in combination with available experimental data and new measurements of the optical absorption spectrum, further corroborate the geometries proposed here for free and defect-bound (bi)polarons.

A photoredox catalysed Heck reaction via hole transfer from a Ru(ii)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg; Gerstmann, Uwe; Meier, Armin; Schmidt, Wolf Gero; Wilhelm, René (RSC Advances)
A hole transfer from an excited Ru unit towards graphene oxide significantly improved the photocatalytic activity of the complexes.
Keywords: General Chemical Engineering; General Chemistry

Toward Efficient Toxic-Gas Detectors: Exploring Molecular Interactions of Sarin and Dimethyl Methylphosphonate with Metal-Centered Phthalocyanine Structures - Aldahhak, Hazem; Powroźnik, Paulina; Pander, Piotr; Jakubik, Wiesław; Dias, Fernando B.; Schmidt, Wolf Gero; Gerstmann, Uwe; Krzywiecki, Maciej (The Journal of Physical Chemistry C)

Vibration-Driven Self-Doping of Dangling-Bond Wires on Si(553)-Au Surfaces - Braun, Christian; Neufeld, Sergej; Gerstmann, Uwe; Sanna, S.; Plaickner, J.; Speiser, E.; Esser, N.; Schmidt, Wolf Gero (Physical Review Letters)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Tetracene Ultrathin Film Growth on Hydrogen-Passivated Silicon - Niederhausen, Jens; MacQueen, Rowan W.; Lips, Klaus; Aldahhak, Hazem; Schmidt, Wolf Gero; Gerstmann, Uwe (Langmuir)

Photochemical Ring Opening of Oxirane Modeled by Constrained Density Functional Theory - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (ACS Omega)

Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Spin-orbit driven electrical manipulation of the zero-field splitting in high-spin centers in solids - Biktagirov, Timur; Gerstmann, Uwe (Physical Review Research)
Keywords: General Engineering

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi; Wilhelm, René; Schmidt, Wolf Gero (Journal of Computational Chemistry)
Density-functional theory calculations of (TiO2)n clusters (n = 1–5) in the gas phase and adsorbed on pristine graphene as well as graphene quantum dots are presented. The cluster adsorption is found to be dominated by van der Waals forces. The electronic structure and in particular the excitation energies of the bare clusters and the TiO2/graphene composites are found to vary largely in dependence on the size of the respective constituents. This holds in particular for the energy and the spatial localization of the highest occupied and lowest unoccupied molecular orbitals. In addition to a substantial gap narrowing, a pronounced separation of photoexcited electrons and holes is predicted in some instances. This is expected to prolong the lifetime of photoexcited carriers. Altogether, TiO2/graphene composites are predicted to be promising photocatalysts with improved electronic and photocatalytic properties compared to bulk TiO2.

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

Quasiparticle and excitonic effects in the optical response of KNbO3 - Schmidt, Falko; Riefer, Arthur; Schmidt, Wolf Gero; Schindlmayr, Arno; Imlau, Mirco; Dobener, Florian; Mengel, Nils; Chatterjee, Sangam; Sanna, Simone (Physical Review Materials)
The cubic, tetragonal, and orthorhombic phase of potassium niobate (KNbO3) are studied based on density-functional theory. Starting from the relaxed atomic geometries, we analyze the influence of self-energy corrections on the electronic band structure within the GW approximation. We find that quasiparticle shifts widen the direct (indirect) band gap by 1.21 (1.44), 1.58 (1.55), and 1.67 (1.64) eV for the cubic, tetragonal, and orthorhombic phase, respectively. By solving the Bethe-Salpeter equation, we obtain the linear dielectric function with excitonic and local-field effects, which turn out to be essential for good agreement with experimental data. From our results, we extract an exciton binding energy of 0.6, 0.5, and 0.5 eV for the cubic, tetragonal, and orthorhombic phase, respectively. Furthermore, we investigate the nonlinear second-harmonic generation (SHG) both theoretically and experimentally. The frequency-dependent second-order polarization tensor of orthorhombic KNbO3 is measured for incoming photon energies between 1.2 and 1.6 eV. In addition, calculations within the independent-(quasi)particle approximation are performed for the tetragonal and orthorhombic phase. The novel experimental data are in excellent agreement with the quasiparticle calculations and resolve persistent discrepancies between earlier experimental measurements and ab initio results reported in the literature.

Excited-state band mapping and momentum-resolved ultrafast population dynamics in In/Si(111) nanowires investigated with XUV-based time- and angle-resolved photoemission spectroscopy - Nicholson, C. W.; Puppin, M.; Lücke, A.; Gerstmann, Uwe; Krenz, Marvin; Schmidt, Wolf Gero; Rettig, L.; Ernstorfer, R.; Wolf, M. (Physical Review B)

Water Splitting Reaction at Polar Lithium Niobate Surfaces - Dues, Christof; Schmidt, Wolf Gero; Sanna, Simone (ACS Omega)

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Structural dynamics upon photoexcitation-induced charge transfer in a dicopper(i)–disulfide complex - Naumova, Maria; Khakhulin, Dmitry; Rebarz, Mateusz; Rohrmüller, Martin; Dicke, Benjamin; Biednov, Mykola; Britz, Alexander; Espinoza, Shirly; Grimm-Lebsanft, Benjamin; Kloz, Miroslav; Kretzschmar, Norman; Neuba, Adam; et al. (Physical Chemistry Chemical Physics)
A study of structural evolution upon photoinduced charge transfer in a dicopper complex with biologically relevant sulfur coordination.

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, C.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Calculation of spin-spin zero-field splitting within periodic boundary conditions: Towards all-electron accuracy - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Erratum: Optical properties of titanium-doped lithium niobate from time-dependent density-functional theory [Phys. Rev. Materials 1, 034401 (2017)] - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)

Vibrational properties of the Au-(3×3)/Si(111) surface reconstruction - Halbig, B.; Liebhaber, M.; Bass, U.; Geurts, J.; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N.; Krenz, Marvin; Neufeld, Sergej; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Temperature stabilizes rough Au/Ge(001) surface reconstructions - Seino, Kaori; Sanna, Simone; Schmidt, Wolf Gero (Surface Science)

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, Christian; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Electric Field Induced Raman Scattering at the Sb–InP(110) Interface: The Surface Dipole Contribution - Esser, Norbert; Schmidt, Wolf Gero (physica status solidi (b))

Signatures of transient Wannier-Stark localization in bulk gallium arsenide - Schmidt, Claudia; Bühler, J.; Heinrich, A.-C.; Allerbeck, J.; Podzimski, R.; Berghoff, Daniel; Meier, Torsten; Schmidt, Wolf Gero; Reichl, C.; Wegscheider, W.; Brida, D.; Leitenstorfer, A. (Nature Communications)

Impact of finite-temperature and condensed-phase effects on theoretical X-ray absorption spectra of transition metal complexes - Müller, Patrick; Karhan, Kristof; Krack, Matthias; Gerstmann, Uwe; Schmidt, Wolf Gero; Bauer, Matthias; Kühne, Thomas D. (Journal of Computational Chemistry)

Plasmon spectroscopy: Robust metallicity of Au wires on Si(557) upon oxidation - Mamiyev, Z.; Lichtenstein, T.; Tegenkamp, C.; Braun, Christian; Schmidt, Wolf Gero; Sanna, S.; Pfnür, H. (Physical Review Materials)

Polytypism driven zero-field splitting of silicon vacancies in 6H-SiC - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe; Yavkin, Boris; Orlinskii, Sergei; Baranov, Pavel; Dyakonov, Vladimir; Soltamov, Victor (Physical Review B)

Spin pairing versus spin chains at Si(553)-Au surfaces - Braun, Christian; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

New pyridinium based ionic dyes for the hydrogen evolution reaction - Konieczna, Dagny D.; Biller, Harry; Witte, Matthias; Schmidt, Wolf Gero; Neuba, Adam; Wilhelm, René (Tetrahedron)

Solving the Bethe-Salpeter equation for the second-harmonic generation in Zn chalcogenides - Riefer, A.; Schmidt, Wolf Gero (Physical Review B)

Si(775)-Au atomic chains: Geometry, optical properties, and spin order - Braun, Christian; Hogan, Conor; Chandola, Sandhya; Esser, Norbert; Sanna, Simone; Schmidt, Wolf Gero (Physical Review Materials)

Polaron optical absorption in congruent lithium niobate from time-dependent density-functional theory - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)
The optical properties of congruent lithium niobate are analyzed from first principles. The dielectric function of the material is calculated within time-dependent density-functional theory. The effects of isolated intrinsic defects and defect pairs, including the NbLi4+ antisite and the NbLi4+−NbNb4+ pair, commonly addressed as a bound polaron and bipolaron, respectively, are discussed in detail. In addition, we present further possible realizations of polaronic and bipolaronic systems. The absorption feature around 1.64 eV, ascribed to small bound polarons [O. F. Schirmer et al., J. Phys.: Condens. Matter 21, 123201 (2009)], is nicely reproduced within these models. Among the investigated defects, we find that the presence of bipolarons at bound interstitial-vacancy pairs NbV−VLi can best explain the experimentally observed broad absorption band at 2.5 eV. Our results provide a microscopic model for the observed optical spectra and suggest that, besides NbLi antisites and Nb and Li vacancies, Nb interstitials are also formed in congruent lithium-niobate samples.

Efficient PAW-based bond strength analysis for understanding the In/Si(111)(8 × 2) - (4 × 1) phase transition - Lücke, Andreas; Gerstmann, Uwe; Kühne, Thomas D.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

LiNbO3 surfaces from a microscopic perspective - Sanna, Simone; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Optically excited structural transition in atomic wires on surfaces at the quantum limit - Frigge, T.; Hafke, B.; Witte, T.; Krenzer, B.; Streubühr, C.; Samad Syed, A.; Mikšić Trontl, V.; Avigo, I.; Zhou, P.; Ligges, M.; von der Linde, D.; Bovensiepen, U.; et al. (Nature)

Current density analysis of electron transport through molecular wires in open quantum systems - Nozaki, Daijiro; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

[Cu6(NGuaS)6]2+ and its oxidized and reduced derivatives: Confining electrons on a torus - Witte, Matthias; Rohrmüller, Martin; Gerstmann, Uwe; Henkel, Gerald; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

On-Surface Site-Selective Cyclization of Corrole Radicals - Tebi, Stefano; Paszkiewicz, Mateusz; Aldahhak, Hazem; Allegretti, Francesco; Gonglach, Sabrina; Haas, Michael; Waser, Mario; Deimel, Peter S.; Aguilar, Pablo Casado; Zhang, Yi-Qi; Papageorgiou, Anthoula C.; Duncan, David A.; et al. (ACS Nano)

X-ray Spectroscopy of Thin Film Free-Base Corroles: A Combined Theoretical and Experimental Characterization - Aldahhak, Hazem; Paszkiewicz, M.; Allegretti, F.; Duncan, D. A.; Tebi, S.; Deimel, P. S.; Casado Aguilar, P.; Zhang, Y.-Q.; Papageorgiou, A. C.; Koch, R.; Barth, J. V.; Schmidt, Wolf Gero; et al. (The Journal of Physical Chemistry C)

Electron paramagnetic resonance calculations for hydrogenated Si surfaces - Rohrmüller, M.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Tuning the conductivity along atomic chains by selective chemisorption - Edler, F.; Miccoli, I.; Stöckmann, J. P.; Pfnür, H.; Braun, Christian; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Molecular Orbital Rule for Quantum Interference in Weakly Coupled Dimers: Low-Energy Giant Conductivity Switching Induced by Orbital Level Crossing - Nozaki, Daijiro; Lücke, Andreas; Schmidt, Wolf Gero (The Journal of Physical Chemistry Letters)

Optical properties of titanium-doped lithium niobate from time-dependent density-functional theory - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)
The optical properties of pristine and titanium-doped LiNbO3 are modeled from first principles. The dielectric functions are calculated within time-dependent density-functional theory, and a model long-range contribution is employed for the exchange-correlation kernel in order to account for the electron-hole binding. Our study focuses on the influence of substitutional titanium atoms on lithium sites. We show that an increasing titanium concentration enhances the values of the refractive indices and the reflectivity.

Consistent atomic geometries and electronic structure of five phases of potassium niobate from density-functional theory - Schmidt, Falko; Landmann, Marc; Rauls, Eva; Argiolas, Nicola; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Advances in Materials Science and Engineering)
We perform a comprehensive theoretical study of the structural and electronic properties of potassium niobate (KNbO3) in the cubic, tetragonal, orthorhombic, monoclinic, and rhombohedral phase, based on density-functional theory. The influence of different parametrizations of the exchange-correlation functional on the investigated properties is analyzed in detail, and the results are compared to available experimental data. We argue that the PBEsol and AM05 generalized gradient approximations as well as the RTPSS meta-generalized gradient approximation yield consistently accurate structural data for both the external and internal degrees of freedom and are overall superior to the local-density approximation or other conventional generalized gradient approximations for the structural characterization of KNbO3. Band-structure calculations using a HSE-type hybrid functional further indicate significant near degeneracies of band-edge states in all phases which are expected to be relevant for the optical response of the material.

Advanced capabilities for materials modelling with Quantum ESPRESSO - Giannozzi, P; Andreussi, O; Brumme, T; Bunau, O; Buongiorno Nardelli, M; Calandra, M; Car, R; Cavazzoni, C; Ceresoli, D; Cococcioni, M; Colonna, N; Carnimeo, I; et al. (Journal of Physics: Condensed Matter)

Vibration eigenmodes of the Au-(5×2)/Si(111) surface studied by Raman spectroscopy and first-principles calculations - Liebhaber, M.; Halbig, B.; Bass, U.; Geurts, J.; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N. (Physical Review B)

Surface induced vibrational modes in the fluorescence spectra of PTCDA adsorbed on the KCl(100) and NaCl(100) surfaces - Paulheim, A.; Marquardt, C.; Sokolowski, M.; Hochheim, M.; Bredow, T.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Physical Chemistry Chemical Physics)
We report a combined experiment-theory study on low energy vibrational modes in fluorescence spectra of perylene-3,4,9,10-tetracarboxylic acid dianhydride (PTCDA) molecules.

LiNbO3 electronic structure: Many-body interactions, spin-orbit coupling, and thermal effects - Riefer, Arthur; Friedrich, Michael; Sanna, Simone; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The influence of electronic many-body interactions, spin-orbit coupling, and thermal lattice vibrations on the electronic structure of lithium niobate is calculated from first principles. Self-energy calculations in the GW approximation show that the inclusion of self-consistency in the Green function G and the screened Coulomb potential W opens the band gap far stronger than found in previous G0W0 calculations but slightly overestimates its actual value due to the neglect of excitonic effects in W. A realistic frozen-lattice band gap of about 5.9 eV is obtained by combining hybrid density functional theory with the QSGW0 scheme. The renormalization of the band gap due to electron-phonon coupling, derived here using molecular dynamics as well as density functional perturbation theory, reduces this value by about 0.5 eV at room temperature. Spin-orbit coupling does not noticeably modify the fundamental gap but gives rise to a Rashba-like spin texture in the conduction band.

LiTaO3 phonon dispersion and ferroelectric transition calculated from first principles - Friedrich, Michael; Schindlmayr, Arno; Schmidt, Wolf Gero; Sanna, Simone (Physica Status Solidi B)
The phonon dispersions of the ferro‐ and paraelectric phase of LiTaO3 are calculated within density‐functional perturbation theory. The longitudinal optical phonon modes are theoretically derived and compared with available experimental data. Our results confirm the recent phonon assignment proposed by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)] on the basis of spectroscopical studies. A comparison with the phonon band structure of the related material LiNbO3 shows minor differences that can be traced to the atomic‐mass difference between Ta and Nb. The presence of phonons with imaginary frequencies for the paraelectric phase suggests that it does not correspond to a minimum energy structure, and is compatible with an order‐disorder type phase transition.

Strain-induced quasi-one-dimensional rare-earth silicide structures on Si(111) - Timmer, F.; Oelke, R.; Dues, C.; Sanna, S.; Schmidt, Wolf Gero; Franz, M.; Appelfeller, S.; Dähne, M.; Wollschläger, J. (Physical Review B)

Experimental and Theoretical High-Energy-Resolution X-ray Absorption Spectroscopy: Implications for the Investigation of the Entatic State - Vollmers, Nora Jenny; Müller, Patrick; Hoffmann, Alexander; Herres-Pawlis, Sonja; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe; Bauer, Matthias (Inorganic Chemistry)

Optical response of the Cu2S2diamond core in Cu2II(NGuaS)2Cl2 - Witte, Matthias; Grimm-Lebsanft, Benjamin; Goos, Arne; Binder, Stephan; Rübhausen, Michael; Bernard, Martin; Neuba, Adam; Gorelsky, Serge; Gerstmann, Uwe; Henkel, Gerald; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Surface vibrational Raman modes of In:Si(111)(4×1)and(8×2)nanowires - Speiser, E.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Temperature-Dependent Hole Mobility and Its Limit in Crystal-Phase P3HT Calculated from First Principles - Lücke, Andreas; Ortmann, Frank; Panhans, Michel; Sanna, Simone; Rauls, Eva; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry B)

Inhomogeneous and Homogeneous Line Broadening of Optical Spectra of PTCDA Molecules Adsorbed at Step Edges of Alkali Halide Surfaces - Paulheim, A.; Marquardt, C.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero; Sokolowski, M. (The Journal of Physical Chemistry C)

Grand canonical Peierls transition in In/Si(111) - Jeckelmann, Eric; Sanna, Simone; Schmidt, Wolf Gero; Speiser, Eugen; Esser, Norbert (Physical Review B)

Rare-earth silicide thin films on the Si(111) surface - Sanna, S.; Dues, C.; Schmidt, Wolf Gero; Timmer, F.; Wollschläger, J.; Franz, M.; Appelfeller, S.; Dähne, M. (Physical Review B)

Density functional theory of the CuA-like Cu2S2 diamond core in Cu 2II(NGuaS)2Cl2 - Witte, M.; Gerstmann, Uwe; Neuba, Adam; Henkel, G.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic size effects studied by transport in single silicide nanowires - Miccoli, I.; Edler, F.; Pfnür, H.; Appelfeller, S.; Dähne, M.; Holtgrewe, K.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

A Bifunctional Electrocatalyst for Oxygen Evolution and Oxygen Reduction Reactions in Water - Schöfberger, Wolfgang; Faschinger, Felix; Chattopadhyay, Samir; Bhakta, Snehadri; Mondal, Biswajit; Elemans, Johannes A. A. W.; Müllegger, Stefan; Tebi, Stefano; Koch, Reinhold; Klappenberger, Florian; Paszkiewicz, Mateusz; Barth, Johannes V.; et al. (Angewandte Chemie International Edition)

Manipulation resolves non-trivial structure of corrole monolayer on Ag(111) - Tebi, Stefano; Aldahhak, Hazem; Serrano, Giulia; Schöfberger, Wolfgang; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold; Müllegger, Stefan (Nanotechnology)

Surface induced vibrational modes in the fluorescence spectra of PTCDA adsorbed on the KCl(100) and NaCl(100) surfaces - Paulheim, A.; Marquardt, C.; Sokolowski, M.; Hochheim, M.; Bredow, T.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Physical Chemistry Chemical Physics)
We report a combined experiment-theory study on low energy vibrational modes in fluorescence spectra of perylene-3,4,9,10-tetracarboxylic acid dianhydride (PTCDA) molecules.

Impurity-Mediated Early Condensation of a Charge Density Wave in an Atomic Wire Array - Yeom, Han Woong; Oh, Deok Mahn; Wippermann, Stefan; Schmidt, Wolf Gero (ACS Nano)

Vibrational properties of LiNb1−xTaxO3 mixed crystals - Rüsing, Michael; Sanna, Simone; Neufeld, Sergej; Berth, Gerhard; Schmidt, Wolf Gero; Zrenner, Artur; Yu, H.; Wang, Y.; Zhang, H. (Physical Review B)
Congruent lithium niobate and lithium tantalate mixed crystals have been grown over the complete compositional range with the Czochralski method. The structural and vibrational properties of the mixed crystals are studied extensively by x-ray diffraction measurements, Raman spectroscopy, and density functional theory. The measured lattice parameters and vibrational frequencies are in good agreement with our theoretical predictions. The observed dependence of the Raman frequencies on the crystal composition is discussed on the basis of the calculated phonon displacement patterns. The phononic contribution to the static dielectric tensor is calculated by means of the generalized Lyddane-Sachs-Teller relation. Due to the pronounced dependence of the optical response on the Ta concentration, lithium niobate tantalate mixed crystals represent a perfect model system to study the properties of uniaxial mixed ferroelectric materials for application in integrated optics.

Phonon dispersion and zero-point renormalization of LiNbO3 from density-functional perturbation theory - Friedrich, Michael; Riefer, Arthur; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
The vibrational properties of stoichiometric LiNbO3 are analyzed within density-functional perturbation theory in order to obtain the complete phonon dispersion of the material. The phonon density of states of the ferroelectric (paraelectric) phase shows two (one) distinct band gaps separating the high-frequency (~800 cm−1) optical branches from the continuum of acoustic and lower optical phonon states. This result leads to specific heat capacites in close agreement with experimental measurements in the range 0–350 K and a Debye temperature of 574 K. The calculated zero-point renormalization of the electronic Kohn–Sham eigenvalues reveals a strong dependence on the phonon wave vectors, especially near Γ. Integrated over all phonon modes, our results indicate a vibrational correction of the electronic band gap of 0.41 eV at 0 K, which is in excellent agreement with the extrapolated temperature-dependent measurements.

Mechanism for nuclear and electron spin excitation by radio frequency current - Müllegger, Stefan; Rauls, Eva; Gerstmann, Uwe; Tebi, Stefano; Serrano, Giulia; Wiespointner-Baumgarthuber, Stefan; Schmidt, Wolf Gero; Koch, Reinhold (Physical Review B)

Single PTCDA molecules on planar and stepped KCl and NaCl(100) surfaces - Aldahhak, Hazem; Schmidt, Wolf Gero; Rauls, E. (Surface Science)

Diindenoperylene adsorption on Cu(111) studied with density-functional theory - Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Interwire coupling forIn(4×1)/Si(111) probed by surface transport - Edler, F.; Miccoli, I.; Demuth, S.; Pfnür, H.; Wippermann, S.; Lücke, A.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Water adsorbate influence on the Cu(110) surface optical response - Baghbanpourasl, Amirreza; Schmidt, Wolf Gero; Denk, Mariella; Cobet, Christoph; Hohage, Michael; Zeppenfeld, Peter; Hingerl, Kurt (Surface Science)

The Cu2O2torture track for a real-life system: [Cu2(btmgp)2O2]2+oxo and peroxo species in density functional calculations† - Rohrmüller, Martin; Hoffmann, Alexander; Thierfelder, Christian; Herres-Pawlis, Sonja; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Nanopatterning on H-Terminated Si(111) Explained as Dynamic Equilibrium of the Chemical Reaction with Methanol - Thissen, Peter; Fuchs, Ehud; Roodenko, Katy; Peixoto, Tatiana; Batchelor, Ben; Smith, Dennis; Schmidt, Wolf Gero; Chabal, Yves (The Journal of Physical Chemistry C)

Influence of Structural Defects and Oxidation onto Hole Conductivity in P3HT - Lücke, A.; Schmidt, Wolf Gero; Rauls, E.; Ortmann, F.; Gerstmann, Uwe (The Journal of Physical Chemistry B)

Barrier-free subsurface incorporation of 3d metal atoms into Bi(111) films - Klein, C.; Vollmers, N. J.; Gerstmann, Uwe; Zahl, P.; Lükermann, D.; Jnawali, G.; Pfnür, H.; Tegenkamp, C.; Sutter, P.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review B)

Structure formation in diindenoperylene thin films on copper(111) - Aldahhak, Hazem; Matencio, S.; Barrena, E.; Ocal, C.; Schmidt, Wolf Gero; Rauls, E. (Physical Chemistry Chemical Physics)
First-principles calculations were combined with scanning tunneling microscopy (STM) measurements to analyze the adsorption of diindenoperylene (DIP) molecules on Cu(111) surfaces.

Modeling atomic force microscopy at LiNbO 3 surfaces from first-principles - Sanna, S.; Dues, C.; Schmidt, Wolf Gero (Computational Materials Science)

Structure formation in diindenoperylene thin films on copper(111) - Aldahhak, Hazem; Matencio, S.; Barrena, E.; Ocal, C.; Schmidt, Wolf Gero; Rauls, E. (Physical Chemistry Chemical Physics)
First-principles calculations were combined with scanning tunneling microscopy (STM) measurements to analyze the adsorption of diindenoperylene (DIP) molecules on Cu(111) surfaces.

Polaronic deformation at theFe2+/3+impurity site inFe:LiNbO3crystals - Sanson, A.; Zaltron, A.; Argiolas, N.; Sada, C.; Bazzan, M.; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

GaNm-plane: Atomic structure, surface bands, and optical response - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Neumann, M. D.; Speiser, E.; Esser, N. (Physical Review B)

A panel of peralkylated sulfur–guanidine type bases: Novel pro-ligands for use in biomimetic coordination chemistry - Neuba, Adam; Rohrmüller, Martin; Hölscher, Rebecca; Schmidt, Wolf Gero; Henkel, Gerald (Inorganica Chimica Acta)

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Modeling LiNbO3 Surfaces at Ambient Conditions - Hölscher, Rebecca; Schmidt, Wolf Gero; Sanna, Simone (The Journal of Physical Chemistry C)

Adsorption of PTCDA on Terraces and at Steps Sites of the KCl(100) Surface - Guo, Q.; Paulheim, A.; Sokolowski, M.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Oxygen adsorbates on the Si(111)4×1-In metallic atomic wire: Scanning tunneling microscopy and density-functional theory calculations - Oh, Deok Mahn; Wippermann, S.; Schmidt, Wolf Gero; Yeom, Han Woong (Physical Review B)

Geometrical and optical benchmarking of copper(II) guanidine-quinoline complexes: Insights from TD-DFT and many-body perturbation theory (part II) - Hoffmann, Alexander; Rohrmüller, Martin; Jesser, Anton; dos Santos Vieira, Ines; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

The atomic structure of ternary amorphous TixSi1−xO2hybrid oxides - Landmann, M; Köhler, T; Rauls, E; Frauenheim, T; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)